Chapter 7 Covenant, compassion and marketisation in healthcare The mastery of Mammon and the service of grace - Hordern, Joshua (Taylor & Francis, 2018)
'No one can serve two masters . . . You cannot serve God and Mammon.' Jesus' famous words, cited to different purposes by Miran Epstein and Adrian Walsh in this volume, provide a starting point for this chapter's constructive argument and critical conversation with the chapters in this middle part. Epstein deploys Jesus' words to deny the possibility of any constructive reconciliation between capitalism and healthcare, contrasting Jesus' saying with the infamous words of Christian conquistadores and with what he claims is the inherently corrupting, master-slave ethic of the Deuteronomic covenant. By contrast, Walsh cites Jesus to explain Judeo- Christian cultural suspicions about money's place in healthcare before delineating the potentially, though not necessarily, corrosive effects of marketisation